Analysis of the Use of Blackbox Ai in the Coding Process in Web Development Courses - Tanggo, Karolina Viviliana; Sogen, Maria Magdalena Beatrice; Hoar, Fenesia; Bay, Febronia Krista Bene (JUPE : Jurnal Pendidikan Mandala, 2025)
In today's digital context, artificial intelligence-based tools such as Blackbox AI are increasingly being used by students to complete programming assignments, especially in the field of web development. Blackbox AI is one form of AI that is widely used by students. This study aims to uncover concerns about students' dependence on Blackbox AI, which is considered to have a negative impact on their ability to code (do programming) during lectures or when completing assignments. In addition, there is concern that students may experience a decline in critical thinking skills due to frequent reliance on assistance in completing each existing assignment. The purpose of this study was to evaluate the extent to which students depend on Blackbox AI and its impact on critical thinking and coding skills. The method used is a quantitative descriptive approach, with data collected through a questionnaire using a Likert scale from 30 sixth semester students in the Informatics Education Study Program, Citra Bangsa University. The results of the descriptive analysis, most students felt significant benefits from utilizing Blackbox AI with an average of 77.6%, but they also faced a dependence of 63.8% and a negative effect on understanding and independence of 57.1%. Concerns about the decline in coding skills due to reliance on AI were also quite high, reaching 48.9%. This finding highlights the importance of using Blackbox AI wisely and integrated with traditional learning, so as not to hinder the development of critical thinking skills and the basics of programming in students.